Human papillomavirus (HPV) vaccines in adults: Learnings from long-term follow-up of quadrivalent HPV vaccine clinical trials - Stephen E. Goldstone (Taylor & Francis Group, 2023)
The risk for acquiring human papillomavirus (HPV) infections and associated diseases is lifelong. An important part of prophylactic HPV vaccine development is durable protection against infection and disease. With comprehensive long-term follow-up (LTFU) in adolescents, men, and women, the quadrivalent HPV (qHPV) vaccine demonstrated durable effectiveness, immunogenicity, and safety, with almost no breakthrough disease. Those who received a placebo during initial trials were offered the qHPV vaccine at study conclusion and continued to be followed in LTFU extensions. In this catch-up vaccination group, LTFU demonstrated protection even in individuals with current or prior HPV infection after approximately 3 years. The initial efficacy and durable long-term effectiveness of the qHPV vaccine have already translated to a real-world reduction in cancer and cancer precursors. To date, there is no evidence of waning protection; evidence suggests that vaccination ultimately provides strong protection against future disease, with effective prophylaxis even among those with past infections.